Taxotere, cisplatin, fluorouracil, and leucovorin (TPFL)as induction chemotherapy for locally advanced squamous cell carcinoma of the head and neck. - Kamnerdsupaphon P. (2014)
This is a phase II clinical study conducted to evaluate the toxicity and efficacy of a 4-day regimen of docetaxel, cisplatin, fluorouracil, and leucovorin (TPFL) in patients with locoregionally advanced squamous cell carcinoma of the head and neck (SCCHN). PATIENTS AND METHODS: Twenty-one previously untreated patients with stage III or IV SCCHN were treated with TPFL. Patients who received a complete response (CR) or partial response (PR) to three cycles of TPFL received definitive radiation therapy. The primary end points were toxicity and response to TPFL. RESULTS: Fifty cycles were administered to 21 patients. The major acute toxicities to TPFL were mucositis, fatigue, and anorexia. Additional major toxicities were neutropenia, anemia, and weight loss. The overall clinical response rate to TPFL was 47.6% , with 19% CRs and 28.6% PRs. In addition, the median time to progression and overall survival time were 49.2 months and 42.7 months, respectively. CONCLUSION: TPFL has an acceptable toxicity profile for patients with locally advanced squamous cell carcinoma of the head and neck and may hold curative potential for some patients with surgically unresectable or medical inoperable situations. OBJECTIVE: To evaluate the efficacy and safety to TPFL regimen for locally advanced squamous cell carcinoma of the head and neck.